H.G. Wells and all things Russian - Diment, Galya (Anthem Press, an imprint of Wimbledon Publishing, 2019)
'H. G. Wells and All Things Russian' examines Wells's keen interest in Russian culture and development, and how Russia and the Soviet Union were, in turn, profoundly influenced by his works and his visits to the country